Variation of Basal EROD Activities in Ten Passerine Bird Species – Relationships with Diet and Migration Status - Rainio, Miia J. (Public Library of Science, 2012)
Inter-specific differences in animal defence mechanisms against toxic substances are currently poorly understood. The ethoxyresorufin-O-deethylase (EROD) enzyme plays an important role in defence against toxic chemicals in a wide variety of animals, and it is an important biomarker for environmental contamination. We compared basal hepatic EROD activity levels among ten passerine species to see if there is inter-specific variation in enzyme activity, especially in relation to their diet and migration status. Migratory insectivores showed higher EROD activity compared to granivores. We hypothesize that the variable invertebrate diet of migratory insectivores contains a wider range of natural toxins than the narrower diet of granivores. This may have affected the evolution of mixed function oxidases (MFO) system and enzyme activities. We further tested whether metabolic rates or relative liver size were associated with the variation in detoxification capacity. We found no association between EROD activity and relative (per mass unit) basal metabolic rate (BMR). Instead, EROD activity and relative liver mass (% of body mass) correlated positively, suggesting that a proportionally large liver also functions efficiently. Our results suggest that granivores and non-migratory birds may be more vulnerable to environmental contaminants than insectivores and migratory birds. The diet and migration status, however, are phylogenetically strongly connected to each other, and their roles cannot be fully separated in our analysis with only ten passerine species.